Keikutsertaan Masyarakat Muslim dalam Upacara Tiwah Agama Hindu Kaharingan di Kota Palangka Raya - Abdul Helim; Unggun Tiara Syahriana (Al-Qisthu: Jurnal Kajian Ilmu-Ilmu Hukum, 2019)
This study tries to answer on kinds of things followed by Dayak Ngaju Tribe Muslim Community Palangka Raya city in Tiwah Ceremony of Hindu Kaharingan and the reasons why they participate on the ceremony. This problem is studied by qualitative description by using cultural and religious approaches. The study results find out that most of Muslim community only participate some series of tiwah ceremony considered to be still tolerated by Islam, meanwhile for some other small parts, they still participated on them but they just do it not by full-hearted. Their participation on the tiwah ceremony is as a honor for their parents and family having their own history in their life. The participation model of Dayak Ngaju Tribe Muslim Community which is only in still tolerated things in Islam activities can be considered as the local Islamic tradition.